The signal peptide of the Junín arenavirus envelope glycoprotein is myristoylated and forms an essential subunit of the mature G1-G2 complex - York, Joanne (2004)
Arenaviruses comprise a diverse family of rodent-borne viruses that are responsible for recurring and emerging outbreaks of viral hemorrhagic fevers worldwide. The Junín virus, a member of the New World arenaviruses, is endemic to the pampas grasslands of Argentina and is the etiologic agent of Argentine hemorrhagic fever. In this study, we have analyzed the assembly and function of the Junín virus envelope glycoproteins. The mature envelope glycoprotein complex is proteolytically processed from the GP-C precursor polypeptide and consists of three noncovalently associated subunits, G1, G2, and a stable 58-amino-acid signal peptide. This tripartite organization is found both on virions of the attenuated Candid 1 strain and in cells expressing the pathogenic MC2 strain GP-C gene. Replacement of the Junín virus GP-C signal peptide with that of human CD4 has little effect on glycoprotein assembly while abolishing the ability of the G1-G2 complex to mediate pH-dependent cell-cell fusion. In addition, we demonstrate that the Junín virus GP-C signal peptide subunit is myristoylated at its N-terminal glycine. Alanine substitution for the modified glycine residue in the GP-C signal peptide does not affect formation of the tripartite envelope glycoprotein complex but markedly reduces its membrane fusion activity. In contrast to the classical view that signal peptides act primarily in targeting nascent polypeptides to the endoplasmic reticulum, we suggest that the signal peptide of the arenavirus GP-C may serve additional functions in envelope glycoprotein structure and trafficking.